2018
DOI: 10.3390/atmos9020062
|View full text |Cite
|
Sign up to set email alerts
|

Day-Night Differences, Seasonal Variations and Source Apportionment of PM10-Bound PAHs over Xi’an, Northwest China

Abstract: Day-night PM 10 -bound PAHs were studied at an urban site of Xi'an from 20 December 2006 to 28 October 2007. The annual mean concentration of nighttime PAHs (285.0 ng m −3 ) was higher than that in daytime (239.4 ng m −3 ). A significant difference of PAH concentrations between daytime and nighttime was found in autumn with a coefficient of divergence (CD) of 0.23 (significant level 0.2). However, no distinct difference was observed in other seasons (with CD values < 0.2), although the difference of PAHs parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 51 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…These results go beyond previous reports, showing that pollutant concentration of night-time is considerably greater than in daytime [25][26][27]. From the scientific point of view, it can be explained by the following statements.…”
Section: Dynamics Of Pm25 and Pm10supporting
confidence: 46%
“…These results go beyond previous reports, showing that pollutant concentration of night-time is considerably greater than in daytime [25][26][27]. From the scientific point of view, it can be explained by the following statements.…”
Section: Dynamics Of Pm25 and Pm10supporting
confidence: 46%
“…Factor 1 explained 54.20% and 50.29% of the total PAHs in PM 2.5 and PM 2.5-10 , respectively, and was mainly loaded by HMW: Cor (87.10%, 85.94%), BghiP (71.88%, 78.54%), IcdP (71.72%, 79.75%), BeP (67.10%, 77.26%), BkF (66.60%, 78.82%), BbF (65.95%, 78.20%), and DahA (63.98%, 71.41%). Therefore, this factor was identified as coal combustion according to previous studies which showed similar PAH loadings [42,48,49].…”
Section: Sources Of Pahs With Positive Matrix Factorization (Pmf)mentioning
confidence: 99%